Stress Management to Reduce Mild Work Stress in Cafe Employees - Lubana Nataghain AlMuhdhar; Djudiyah, Djudiyah (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
The cafe industry is part of a rapidly growing and competitive service sector, fueled by the rise of coffee consumption and social activities in various cities. Service-oriented work environments are characterized by high emotional demands, a fast-paced work pace, and pressure to ensure quality service, making work stress a critical issue in human resource management. Cafe employees, particularly baristas and waiters, are on the front lines of customer interaction and are therefore susceptible to mild work stress, which is often considered normal. However, persistent, poorly managed mild work stress can potentially develop into emotional exhaustion, decreased psychological well-being, and decreased performance. This study aims to examine the role of stress management in reducing mild work stress levels among cafe employees and its implications for psychological well-being and employee performance. This study is based on a review of empirical literature on work stress in the service sector and the effectiveness of stress management interventions in the workplace. Stress management is understood as a planned effort to identify sources of stress, modify work stress, and strengthen employees' coping abilities. The study results indicate that stress management interventions, such as coping skills training, relaxation techniques, and mindfulness approaches, are effective in reducing work stress and improving employee well-being. Organizational support through fair work arrangements and supportive leadership also strengthens the effectiveness of these interventions.